Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan Kantor Pos Durenan Kabupaten Trenggalek - Dea Nurita Febriana; Moh. Gufron (Economic Reviews Journal, 2024)
This research aims to determine the effect of service quality and promotion on customer satisfaction at the Durenan POS Office, Trenggalek Regency. This research uses a quantitative approach with the population being visitors to the Durenan POS Office, Trenggalek Regency. The sampling method in the research was non-probability sampling, using accidental sampling of 100 respondents. Data was obtained through a questionnaire and analyzed using the SPSS application with multiple linear regression analysis. The research results show that partially service quality has a positive and significant effect on customer satisfaction with t count > t table (2.657 > 1.985) and a significance value of 0.009 < 0.05. Promotion has a positive and significant effect on customer satisfaction with t count > t table (16.210 > 1.985) and a significance value of 0.000 < 0.05. Meanwhile, simultaneously, service quality and promotion have a positive and significant effect on customer satisfaction with calculated f > f table (210.030 > 3.939) and a significance value of 0.000 < 005. The coefficient of determination shows 0.809. This shows that 80.9% of changes in customer satisfaction are influenced by service quality and promotions. Meanwhile, the remaining 19.1% is due to other variables outside those studied.